Psychological Symptoms and Concerns Experienced by International Students: Outreach Implications for Counseling Centers - Poyrazli, Senel (Journal of International Students, 2015)
This study examines psychological symptoms and concerns experienced by international students. Participants identified with a variety of psychological symptoms and concerns. The top three were related to academics (71%), career (60%), and stress (43%). In addition, 34% of the participants indicated being concerned about depression and/or anxiety. For married students, the top three concern areas were related to academics, career, and stress, but 27% of participants also indicated experiencing couple and marital problems. Implications for outreach activities for counseling centers are discussed in light of these findings.